KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) BERBASIS ETNOMATEMATIKA - Moh. Rizki Yuniardi Basuni (Integral : Pendidikan Matematika, 2023)
Mathematical communication skills is important to develop in students, because they have an important role in understanding a problem. Mathematical communication skills can be improved by learning Contextual Teaching and Learning (CTL) based on ethnomathematics with learning concepts that help teachers relate learning materials to students' real world situations. This study aims to develop indicators of mathematical communication skills and ethnomathematical-based Contextual Teaching and Learning (CTL) learning steps that can improve students' mathematical communication skills. The research method used in this study is the Systematic Literature Review (SLR) method. This method identifies, examines, evaluates, and interprets existing research. Based on the literature review, several indicators of students' mathematical communication skills were found, namely interpreting pictures into mathematical ideas, expressing mathematical ideas in the form of pictures and expressing mathematical ideas in their own statements. The ethnomathematical-based Contextual Teaching and Learning (CTL) model can improve students' mathematical communication skills. Keywords: mathematical communication, CTL, Ethnomathematics